Higher Cerebral Small Vessel Disease Burden in Patients With Small Intracerebral Hemorrhage - Wang, Zi-Jie; Zhao, Rui; Hu, Xiao; Yang, Wen-Song; Deng, Lan; Lv, Xin-Ni; Li, Zuo-Qiao; Cheng, Jing; Pu, Ming-Jun; Tang, Zhou-Ping; Wu, Guo-Feng; Zhao, Li-Bo; et al. (Frontiers in Neuroscience, 2022)
Objective To investigate the association between cerebral small vessel disease (SVD) and hematoma volume in primary intracerebral hemorrhage (ICH). Methods Patients from a prospective ICH cohort were enrolled. Admission and follow-up CT scan within 72 h after onset were reviewed to calculate the final hematoma volume. We evaluated cortical superficial siderosis and the global SVD score, including white matter hyperintensities, lacunes, enlarged perivascular space, and cerebral microbleeds on MRI. We conducted the multivariate logistic regression analyses to explore the association between SVD markers and small ICH, as well as hematoma volume. Hematoma location was stratified into lobar and non-lobar for subgroup analysis. Results A total of 187 patients with primary ICH (mean age 62.4 ± 13.4 years, 67.9% male) were enrolled. 94 (50.2%) patients had small ICH. The multivariate logistic regression analysis showed an association between global SVD score and small ICH [adjusted odds ratio (aOR) 1.27, 95% CI 1.03–1.57, p = 0.027] and a trend of higher global SVD score towards non-lobar small ICH (aOR 1.23, 95% CI 0.95–1.58, p = 0.122). In the multivariate linear regression analysis, global SVD score was inversely related to hematoma volume of all ICH (β = −0.084, 95% CI −0.142 to −0.025, p = 0.005) and non-lobar ICH (β = −0.112, 95% CI −0.186 to −0.037, p = 0.004). Lacune (β = −0.245, 95% CI −0.487 to −0.004, p = 0.046) was associated with lower non-lobar ICH volume. Conclusion Global SVD score is associated with small ICH and inversely correlated with hematoma volume. This finding predominantly exists in non-lobar ICH.